Berman and Toury: The Translating and Translatability of Research Frameworks - Brownlie, Siobhan (TTR)

(untitled) (Association canadienne de traductologie, 2003)
AbstractAn initial discussion of Kuhn, Lyotard, and Boothman offers a set of ideas on how and to what extent one research framework can be ‘translated’ into another. Berman’s and Toury’s frameworks for translation research are then examined using some concepts from the above-mentioned theorists, and also concepts from interlingual translation theory. In highly significant ways Berman’s and Toury’s frameworks are incompatible because of the incommensurability of basic ideas underpinning their frameworks. There is, however, some partial equivalence of concepts, in part brought about through evolution of the theories over time. When Berman has ‘translated’ Toury in the sense of discussing his ideas, we find phenomena analogous to those found in interlingual translation: equivalence, transference, shifts, naturalizing, and mistranslation. No doubt if Toury were to ‘translate’ Berman, similar traits would occur. The study supports a nuanced version of Lyotard’s theory: non-absolute incommensurability between discourses or research frameworks.